The Effect of Pec Deck Flyes and Cable Crossover Exercises on Arm Muscle Strength and Tennis Forehand - Maulidin, Maulidin; Summinar, Tiassari Janjang; Syariofeddin, Elya Wibawa (Jurnal Ilmiah Mandala Education (JIME), 2025)
The purpose of this study was to determine the effect of Pec Deck Flyes and Cable Crossover training on Arm Muscle Strength and Forehand in male tennis players. This type of research is an experimental study using "Randomized Control Group Pretest-Posttest Design". The population in this study were 30 male tennis players. Then divided into 3 groups, experimental group I was given Pec Deck Flyes treatment, experimental group II was given Cable Crossover treatment and the control group was given conventional treatment. To determine the strength of the arm muscles, each subject was given a push-up test for 30 seconds and for forehand results, the subjects were given the opportunity to hit 15 balls with the forehand technique. Based on the Multivariate analysis, testing the equality of variance-covariance in both dependent variables together using the Box's Test Of Equality Of Covariance Matrices, a significance value of 0.130> 0.05 was obtained, because the Box's value was greater than alpha 0.05, then the variance-covariance were the same. Testing the equality of variance-covariance on both dependent variables individually using the Levene Test Of Error Variances number for arm muscle strength obtained a significance value of 0.134> 0.05 and a significance value for forehand results of 0.296> 0.05, because the significance value is greater than alpha 0.05. It can be concluded that both dependent variables have different Variance-Covariance Matrices in the independent variable group. The difference between groups using the Wilks' Lambda test obtained a significance value of 0.00 <0.05. Because the Wilks' Lambda significance value is smaller than alpha 0.05, it can be concluded that there is a difference in the increase in arm muscle strength and forehand results.Keywords: Training, Pec deck Flyes, Cable Crossovr, Arm Muscle Strength, and forehand.